2022
DOI: 10.3390/nu14194142
|View full text |Cite
|
Sign up to set email alerts
|

Does Consumption of Ultra-Processed Foods Matter for Liver Health? Prospective Analysis among Older Adults with Metabolic Syndrome

Abstract: Non-alcoholic fatty liver disease (NAFLD) includes a spectrum of liver alterations that can result in severe disease and even death. Consumption of ultra-processed foods (UPF) has been associated with obesity and related comorbidities. However, the link between UPF and NAFLD has not been sufficiently assessed. We aimed to investigate the prospective association between UPF consumption and liver health biomarkers. Methods: We followed for 1 year 5867 older participants with overweight/obesity and metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 62 publications
(93 reference statements)
0
24
0
Order By: Relevance
“…Even in children and adolescents, metabolic parameters such as increased serum total cholesterol, triglyceride (18) and waist https://doi.org/10.1017/S0007114522003956 Published online by Cambridge University Press Accepted manuscript circumference (19) were significantly associated with the contribution of UPF. Although UPF consumption was associated with a significantly greater fatty liver index among older participants with overweight/obesity and metabolic syndrome (20), there is still a lack of evidence-based data to explain this association in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Even in children and adolescents, metabolic parameters such as increased serum total cholesterol, triglyceride (18) and waist https://doi.org/10.1017/S0007114522003956 Published online by Cambridge University Press Accepted manuscript circumference (19) were significantly associated with the contribution of UPF. Although UPF consumption was associated with a significantly greater fatty liver index among older participants with overweight/obesity and metabolic syndrome (20), there is still a lack of evidence-based data to explain this association in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…The main demographics and results of the studies included in this systematic review and meta-analysis are shown in Table 1 . The studies included participants from Asia [ 24 ], the USA [ 34 , 35 ] and Europe [ 25 , 26 , 27 , 36 , 37 , 38 ]. Three of the included studies were longitudinal, with follow up times ranging from 1 to 25 years [ 24 , 26 , 34 ], three were case-control [ 35 , 36 , 37 ], and three were cross-sectional in design [ 25 , 27 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included participants from Asia [ 24 ], the USA [ 34 , 35 ] and Europe [ 25 , 26 , 27 , 36 , 37 , 38 ]. Three of the included studies were longitudinal, with follow up times ranging from 1 to 25 years [ 24 , 26 , 34 ], three were case-control [ 35 , 36 , 37 ], and three were cross-sectional in design [ 25 , 27 , 38 ]. Sample sizes ranged from 286 to 32,448 [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations